The effect of intelligent manufacturing on remanufacturing decisions. (April 2023) - Li, Kai; Zhang, Limin; Fu, Hong; Liu, Bohai
Abstract: We consider that intelligent manufacturing can reduce the cost of the new product by improving production efficiency, which creates a manufacturing benefit. Meanwhile, the application of intelligent manufacturing technology improves the accuracy of remanufacturing, resulting in the remanufacturing benefit that reduces the remanufacturing cost. We establish dynamic game models to investigate the effect of intelligent manufacturing on remanufacturing decisions under three remanufacturing manners: retailer remanufacturing, manufacturer remanufacturing, and cooperative remanufacturing. Analyzing the equilibrium decision, economic performance, and enthusiasm for engagement in remanufacturing under different remanufacturing models, we show that intelligent remanufacturing does not always facilitate remanufacturing. Specifically, if the retailer remanufactures without purchasing the manufacturer's technical service, intelligent manufacturing reduces its enthusiasm for engagement in remanufacturing. In this case, the manufacturer does not prefer authorizing the retailer to remanufacture. Furthermore, our results illustrate that if the retailer remanufactures by purchasing the manufacturer's technical service, the manufacturer prefers to authorize the retailer to remanufacture when the initial cost of the remanufactured product is lower. In this case, the retailer can also remanufacture more used products than the manufacturer. However, when the initial cost of the remanufactured product is higher, the manufacturer will not authorize the retailer to remanufacture unless it can obtain a sufficient share of the remanufacturing benefit. Our conclusions offer insights for supply chain managers in their remanufacturing decisions. Highlights: The dynamic game models are developed to study three remanufacturing manners. The effect of intelligent manufacturing on remanufacturing decisions is obtained. The remanufacturing decisions are affected by symmetric and asymmetric information structures. Intelligent remanufacturing does not always facilitate remanufacturing.